Current State of the Art in Ventricle Tissue Engineering - Birla, Ravi K. (Frontiers in Cardiovascular Medicine, 2020)
The field of ventricle tissue engineering is focused on bioengineering highly function left ventricles that can used as model systems for basic cardiology research and for cardiotoxicity testing. In this article, we review the current state of art in the field of ventricle tissue engineering and discuss different strategies that have been used to bioengineer ventricles. Based on this body of literature, there are now common themes in the field that provide guidance for future directives, also presented in this article.